Helminth Eggs as a Magnetic Biomaterial: Introducing a Recognition Probe - Shaali, Ruhollah; Doroodmand, Mohammad Mahdi; Moazeni, Mohmmad (Frontiers in Veterinary Science, 2022)
Parasitic helminths, despite their known negative impact (biomaterial) on human health and animal production, have fascinating features. In this study, we find fantastic magnetic properties in several forms: inductor [between 20.10 and 58.85 (±2.50) H], source of detectable electrical voltage [from +0.5 to 7.3 (±0.1) V, vs. the ground, GND, measured by an AVO meter] and different inductor magnitude [between 3.33 and 41.23 (±0.76)] μH, detected by electrochemical impedance spectroscopy as well as frequency scannable electromagnetic wave horn) in several frequencies (including 100, 120, Hz, and 1, 10, 100 kHz) in “Fasciola hepatica”, “Parascaris equorum” (with and without larvae), “Dicrocoelium dendriticum,” “Taenia multiceps”, and “Moniezia expansa” eggs. This claim is attributed to some surprising characteristics, including superior inductance and intrinsic magnetic susceptibility. This feature along with a close relationship to helminth egg structure, is a novel probe with acceptable reproducibility (RSD > 8.0%) and high enough trustworthiness for adequate differentiation in their magnitudes, relatively. These traits were measured by the “Single Cell Rrecording” methodology using a three-microelectrode system, implanted to each egg at the Giga ohm sealed condition (6.08 ± 0.22 GΩ cm−1, n = 5). The reliability of these results was further confirmed using multiple calibrated instruments such as a high-resolution inductance analyzer, LCR meter, impedance spectrometer, potentiometer, and an anomalous Hall effect (Magnetic field density) sensor. In addition, the critical role played (Synergistic Effect) by water-like molecules as the intermediate medium, besides the partial influence of other compounds such as dissolved oxygen, are investigated qualitatively, and specific relation between these molecules and magnetic field creation in helminth eggs was proved. These intrinsic characteristics would provide novel facilitators for efficient arriving at the researchable bio-based magnetic biomaterials, besides innovative and real-time identification probes in the “Parasitology” fields.